Evaluation of Hemodynamic Parameters as Predictors of Glaucoma Progression - Ingrida Januleviciene; Rita Ehrlich; Brent Siesky; Irena Nedzelskiene; Alon Harris (Journal of Ophthalmology)
Purpose. To evaluate hemodynamic parameters as possible predictors for glaucoma progression. Methods. An 18-month randomized double-masked cohort study including 30 open-angle glaucoma patients receiving fixed-combination treatment with Dorzolamide/Timolol (DTFC) or Latanoprost/Timolol (LTFC) (n=15 per group) was performed. Intraocular pressure (IOP), arterial blood pressure (BP), ocular and diastolic perfusion pressures (OPP, DPP), color Doppler imaging, pulsatile ocular blood flow analysis, scanning laser polarimetry, and Humphrey visual field evaluations were included. Results. Both treatments showed statistically similar IOP reduction. Six patients in DTFC and 7 in LTFC group met glaucoma progression criteria. DTFC group had higher OPP, DPP, and lower vascular resistivity indices as compared to the LTFC. Progressing patients had higher nerve fiber index, lower systolic BP, OPP, DPP, higher ophthalmic and central retinal artery vascular resistance, and lower pulse volume (P<.05; t-test). Conclusions. Structural changes consistent with glaucoma progression correlate with non-IOP-dependent risk factors.